Aldo Tagliaferro 1970: la mostra di una mostra come doppia verifica - Fontana, Sara (Rivista di studi di fotografia. Journal of Studies in Photography, 2018)
The essay reconstructs the gestation, the exhibitions and critical reception of Verifica di una mostra, a work by Aldo Tagliaferro (Legnano, 1936-Parma, 2009) designed as a real time verification of rituals that accompany the creation of an exhibition in an art gallery, specifically his solo exhibition at the Galleria La Bertesca in Genoa in January 1970. This work inaugurates a conceptual phase of the artist’s investigation and remains a milestone in Italian visual culture of the 1970s, offering one of the first reflections on the ability of art to transform the inert spectator into a participant observer, a co-author, and a critic.